2017
DOI: 10.15195/v4.a17
|View full text |Cite
|
Sign up to set email alerts
|

A Taste of Inequality: Food's Symbolic Value across the Socioeconomic Spectrum

Abstract: Scholars commonly account for dietary disparities across socioeconomic status (SES) using structural explanations that highlight differences in individuals' wealth, income, or location. These explanations emphasize food's material value. But food also carries symbolic value. This article shows how food's symbolic value helps drive dietary disparities. In-depth interviews with 160 parents and adolescents and 80 hours of observations with four families demonstrate how a family's socioeconomic position in part sh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0
4

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(80 citation statements)
references
References 50 publications
4
72
0
4
Order By: Relevance
“…The concern was more on satisfying hunger, and to ful l the desire of food with good taste. Therefore, there was a higher tendency to buy high sugar foods and SSBs (23). It was also shown that parental in uence on the intake of a child's drinks may be linked to the knowledge associated with diet and health (24).…”
Section: Discussionmentioning
confidence: 99%
“…The concern was more on satisfying hunger, and to ful l the desire of food with good taste. Therefore, there was a higher tendency to buy high sugar foods and SSBs (23). It was also shown that parental in uence on the intake of a child's drinks may be linked to the knowledge associated with diet and health (24).…”
Section: Discussionmentioning
confidence: 99%
“…The ascendance of a narrow set of feeding expectations takes place against a backdrop of public anxiety about the decline of the family meal (Bowen, Elliott, & Brenton, 2014;Murcott, 2012;Musick & Meier, 2012;Trubek, 2017), a widespread (and incorrect) perception that the poor rely more on convenience food than middle-class consumers (Zagorsky & Smith, 2017), and growing gaps in the "dietary quality" of the rich and the poor (Rehm, Penalvo, Afshin, & Mozaffarian, 2016;Wang et al, 2014). Diet disparities are linked to variations in access to healthy food as well as differences in the symbolic ascriptions people attach to food (Backett-Milburn, Wills, Roberts, & Lawton, 2010;Fielding-Singh, 2017).…”
Section: Motherhood Feeding Practices and Obesitymentioning
confidence: 99%
“…Past research has documented the practical, moral, and symbolic components of low-income mothers' foodwork (e.g., Backett-Milburn et al, 2010;Chen, 2016;Daniel, 2016;Fielding-Singh, 2017;Wright et al, 2015). Yet many low-income women also encounter institutional monitoring and regulation around food and parenting.…”
Section: Motherhood Feeding Practices and Obesitymentioning
confidence: 99%
See 1 more Smart Citation
“…Таким образом, не только вкус [32], но и время разносит людей по разным социальным слоям, оставляя некоторым возможность накапливать социальный и культурный капитал, что в конечном счете и определяет их габитус. У низших социальных слоев большую часть времени занимает работа (у кормильца) или ведение хозяйства.…”
Section: вторая черта заключается в том что в декларации принципов пunclassified